Androgen Receptor Phosphorylation at Serine 308 and Serine 791 Predicts Enhanced Survival in Castrate Resistant Prostate Cancer Patients - McCall, Pamela (MDPI, 2013)
We previously reported that AR phosphorylation at serine 213 was associated with poor outcome and may contribute to prostate cancer development and progression. This study investigates if specific AR phosphorylation sites have differing roles in the progression of hormone naïve prostate cancer (HNPC) to castrate resistant disease (CRPC). A panel of phosphospecific antibodies were employed to study AR phosphorylation in 84 matched HNPC and CRPC tumours. Immunohistochemistry measured Androgen receptor expression phosphorylated at serine residues 94 (pAR(94)), 308 (pAR(308)), 650(pAR(650)) and 791 (pAR(791)). No correlations with clinical parameters were observed for pAR(94) or pAR(650) in HNPC or CRPC tumours. In contrast to our previous observation with serine 213, high pAR(308) is significantly associated with a longer time to disease specific death (p = 0.011) and high pAR(791) expression significantly associated with a longer time to disease recurrence (p = 0.018) in HNPC tumours and longer time to death from disease recurrence (p = 0.040) in CRPC tumours. This observation in CRPC tumours was attenuated in high apoptotic tumours (p = 0.022) and low proliferating tumours (p = 0.004). These results demonstrate that understanding the differing roles of AR phosphorylation is necessary before this can be exploited as a target for castrate resistant prostate cancer.